2009
DOI: 10.1063/1.3091289
|View full text |Cite
|
Sign up to set email alerts
|

B activation and clustering in ion-implanted Ge

Abstract: Experimental studies about electrical activation and clustering of B implanted in crystalline Ge (c-Ge) are reported. To this aim, we structurally and electrically investigated c-Ge samples implanted at different temperatures with B at 35 keV in the high-concentration dopant regime (0.67–25×1020 B/cm3). We elucidated that a high level of damage, in the form of amorphous pockets, favors the electrical activation of the dopant, and a complete activation was achieved for properly chosen implant conditions. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 22 publications
3
27
0
Order By: Relevance
“…[2][3][4] In recent years, several studies have investigated the electrical behavior of ion implanted B in both crystalline (c-Ge) and preamorphized (PA-Ge) Ge. [5][6][7][8][9][10][11] Similar to Si, it has been shown that preamorphization increases dopant activation during the solid phase epitaxial growth (SPEG) process. 6 In addition, a modest 360 C anneal results in a high level of boron activation 7 which remains stable for anneals up to 550 C for 1 h. 9 However, the majority of the experiments published in the literature have used high energy B þ implants that are not directly relevant for ultrashallow junctions.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] In recent years, several studies have investigated the electrical behavior of ion implanted B in both crystalline (c-Ge) and preamorphized (PA-Ge) Ge. [5][6][7][8][9][10][11] Similar to Si, it has been shown that preamorphization increases dopant activation during the solid phase epitaxial growth (SPEG) process. 6 In addition, a modest 360 C anneal results in a high level of boron activation 7 which remains stable for anneals up to 550 C for 1 h. 9 However, the majority of the experiments published in the literature have used high energy B þ implants that are not directly relevant for ultrashallow junctions.…”
Section: Introductionmentioning
confidence: 99%
“…8 As far as technological requirements are considered, B in Ge behaves almost diffusionless 9 and high activation levels can be achieved after annealing B-implanted preamorphized Ge. 10,11 The low B diffusion, which is associated with a diffusion activation enthalpy exceeding the value of Ge self-diffusion, 9 can be explained with both the vacancy and interstitialcy mechanisms. In the case vacancies ͑V͒ mediate B diffusion, the high activation enthalpy reflects a repulsive interaction between B and V due to, e.g., local stress and/or the charge states of the point defects involved in the defect reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Incomplete activation and B:Ge cluster formation following deep (≥ 35 keV) B + implants into crystalline Ge is observed, but the inactive fraction appears to be much more significant with shallow implants (5,6,15).…”
Section: Introductionmentioning
confidence: 99%